MEKANISME KOPING DALAM MENURUNKAN KADAR GLUKOSA DARAH PASIEN DIABETES MELLITUS DI POLIKLINIK PENYAKIT DALAM RSUD DR. R. KOESMA TUBAN - Su’udi; Hadi Purwanto; Yasin Wahyu Rianto (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2017)
Diabetes and stress are the two things are interrelated, because of the stress that occurs in diabetics can lead to increased blood glucose levels, and therefore the ability of patients with diabetes to coping mechanisms do have a positive effect on the emotional well-being and physical condition of diabetics. Stress has become one of the factors that appear in patients with Diabetes Mellitus (DM).Stress affects the DM disease because it affects the decline and the level of blood glucose levels. The ability to deal with stress is different depending on each individual's coping abilities possessed. The purpose of this study was to analyze the relationship coping mechanisms DM patients with a decrease in blood glucose levels. This study is a quantitative, descriptive correlative study method with cross sectional approach. Conducted at the Polyclinic Internal Medicine Hospital Dr. R. Koesma Tuban, in August until October 2016. The sampling procedure using Non Probability Sampling technique (purposive sampling), the number of samples are 63 respondents. Data were analyzed using univariate, bivariate analysis using chi square test, data collection is done by using a questionnaire and observation sheet. Chi Square test results obtained by value p = 0.000, which means that there is a relationship between coping mechanisms DM patients with a decrease in blood glucose levels. Their relationship coping mechanisms DM patients with decreased blood glucose levels, we need a coping mechanism either / adaptive by DM patients, so that patients with diabetes were able to comply with the rules about healthy lifestyles diabetic patient, so that blood glucose levels in diabetic patient can be derived which is ultimately DM complications can be avoided.